2013
DOI: 10.1093/jxb/ert023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of root response to phosphorus supply from morphology to gene analysis in field-grown wheat

Abstract: The adaptations of root morphology, physiology, and biochemistry to phosphorus supply have been characterized intensively. However, characterizing these adaptations at molecular level is largely neglected under field conditions. Here, two consecutive field experiments were carried out to investigate the agronomic traits and root traits of wheat (Triticum aestivum L.) at six P-fertilizer rates. Root samples were collected at flowering to investigate root dry weight, root length density, arbusular-mycorrhizal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 53 publications
(62 reference statements)
4
86
2
Order By: Relevance
“…However, enhanced induction of TaPht1 transcripts might be either a short-term adaptation to local P depletion or unevenly distributed patterns of P availability. High persistent induction during severe long-term scarcity as an adaptation mechanism seems questionable and should be investigated on field-grown crops as performed by Teng et al (2013). Enhancing P acquisition by over-expressing phosphate transporter genes has been reported in tobacco cell cultures (Mitsukawa et al 1997) but could not be confirmed at the plant level (Rae et al 2004).…”
Section: P I Acquisition Via Phosphate Transportersmentioning
confidence: 99%
See 4 more Smart Citations
“…However, enhanced induction of TaPht1 transcripts might be either a short-term adaptation to local P depletion or unevenly distributed patterns of P availability. High persistent induction during severe long-term scarcity as an adaptation mechanism seems questionable and should be investigated on field-grown crops as performed by Teng et al (2013). Enhancing P acquisition by over-expressing phosphate transporter genes has been reported in tobacco cell cultures (Mitsukawa et al 1997) but could not be confirmed at the plant level (Rae et al 2004).…”
Section: P I Acquisition Via Phosphate Transportersmentioning
confidence: 99%
“…A potential candidate target would be characterised by being a key factor in the molecular mechanism of the P starvation response, adaptation and genetic diversity responsible for low P tolerance, keeping in mind that there is a need for different strategies in low-input and high-input systems, focusing more on PAE or PUE respectively. Teng et al (2013) investigated the expression profiling of known P starvation-induced genes in wheat under different levels of P fertiliser and soil Olsen P, proving that the turning point for the genetic response was the critical P level. This observation leads to a more general model (Fig.…”
Section: Potential Targets For Genetic Improvementmentioning
confidence: 99%
See 3 more Smart Citations